2016
DOI: 10.1007/s00417-016-3298-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional evaluation of an iridotomy in primary angle closure eyes

Abstract: This comprehensive functional evaluation of laser iridotomy in early PAC eyes showed a significant reduction in the pupillary block component of IOP response to provocative testing, possibly decreasing IOP fluctuations over time. An iridotomy does not, however, significantly change mean IOP or diurnal phasing of IOP in PAC eyes. Eyes with a very narrow angle or a thick lens may continue to have angle closure due to other pathomechanisms for angle closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…15 Eyes with thicker iris, higher iris insertion and thicker lens will still have narrow angle after laser Iridotomy. 16 Greatest effect of Laser Peripheral Iridotomy is seen in eyes with greatest baseline pupil block. 17 Laser trabeculoplasty has role in narrow angle as well once angle is opened by laser iridotomy or Iridoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…15 Eyes with thicker iris, higher iris insertion and thicker lens will still have narrow angle after laser Iridotomy. 16 Greatest effect of Laser Peripheral Iridotomy is seen in eyes with greatest baseline pupil block. 17 Laser trabeculoplasty has role in narrow angle as well once angle is opened by laser iridotomy or Iridoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…[29] Interestingly, it has been reported that the extent of PAS did not correlate with the rise in IOP seen on provocative tests such as the dark room test, pharmacologic mydriasis, and the Valsalva test in patients with PAC. [18] Parameters identifying eyes that continue to develop angle closure after an iridotomy would lead to better management of PAC. Although LPI is claimed to prevent PACS progression to PAC or PACG, it is not guaranteed, as some patients progress despite successful LPI.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in IOP of 6 mmHg from baseline was considered a positive result on both provocative tests. [18] Secondary outcomes were refraction ocular biometric parameters obtained using Lenstar LS 900 (Haag-Streit AG, Koeniz, Switzerland) and Pentacam HR (Oculus, Wetzlar, Germany) optical biometers. The following parameters were collected from the Lenstar biometer: mean keratometry (Km), keratometric astigmatism (Ka), central corneal thickness (CCT), axial length (AL), and lens thickness (LT).…”
Section: Measurementsmentioning
confidence: 99%
“…Eyes with a very narrow angle or a thick lens may continue to have angle closure due to other pathomechanisms for angle closure. [ 13 ] Iridotomy is done for therapeutic purposes to relieve an acute angle closure attack and to relieve the raised IOP in eyes with iris bombe due to secondary angle closure. …”
Section: Nd:yag Laser Peripheral Iridotomy (Lpi)mentioning
confidence: 99%
“…Eyes with a very narrow angle or a thick lens may continue to have angle closure due to other pathomechanisms for angle closure. [ 13 ]…”
Section: Nd:yag Laser Peripheral Iridotomy (Lpi)mentioning
confidence: 99%